2019
DOI: 10.3390/nu11081920
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Patterns of Patients with Chronic Kidney Disease: The Influence of Treatment Modality

Abstract: Background: We analyzed the dietary patterns of Brazilian individuals with a self-declared diagnosis of chronic kidney disease (CKD) and explored associations with treatment modality. Methods: Weekly consumption of 14 food intake markers was analyzed in 839 individuals from the 2013 Brazil National Health Survey with a self-declared diagnosis of CKD undergoing nondialysis (n = 480), dialysis (n = 48), or renal transplant (n = 17) treatment or no CKD treatment (n = 294). Dietary patterns were derived by explora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 39 publications
1
16
0
1
Order By: Relevance
“…Firstly, the degree of compliance with dietary guidelines needs to be determined to define a diet before the predefined food patterns are assessed as either promoting or being detrimental to health. Several recent studies associate certain factors with what are known as dietary patterns [ 38 , 39 , 40 ]. In this study too, a number of factors were associated with dietary patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the degree of compliance with dietary guidelines needs to be determined to define a diet before the predefined food patterns are assessed as either promoting or being detrimental to health. Several recent studies associate certain factors with what are known as dietary patterns [ 38 , 39 , 40 ]. In this study too, a number of factors were associated with dietary patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Admittedly, it is controversial whether aquatic product intake takes a positive effect on health or not. Fernanda Santin et al de ned an "unhealthy" pattern including sh intake based on exploratory factor analysis in a cross-section study and concluded that "unhealthy" patterns lead to diminished renal function and developed CKD [38]. While in a cohort study enrolling 4133 healthy individuals aged 18-30 years, Inwhee Park et al found that the intake of LCω-3PUFA, which mainly provided by sh, was inversely associated with the development of CKD [39].…”
Section: Discussionmentioning
confidence: 99%
“…The present Special Issue on “Targeted Nutrition in Chronic Disease” includes three reviews [ 2 , 3 , 4 ] and seven original research articles [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. A meta-analysis on coffee intake and obesity suggested that higher coffee intake was associated with modestly lower body mass index (BMI) and waist circumference in men but not in women [ 2 ].…”
mentioning
confidence: 99%
“…The inclusion of additional dietary information enhanced the performance of the AHEI–HD index [ 8 ], which could be used to provide dietary recommendations to hemodialysis patients and to obtain a better prediction of the mortality outcome in patients with a low AHEI–HD compared to patients with a high AHEI–HD. In another study on chronic kidney disease, the weekly consumption of 14 food intake markers was mapped in 839 Brazilian individuals with a self-declared diagnosis who were undergoing different treatment modalities [ 9 ]. The food patterns among patients with chronic kidney disease are diverse [ 19 ] and influenced by both sociodemographic and geographical variables [ 20 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation